A Postcolonial Marxist Critique of the River‐as‐Subject: Situating the Atrato River in Its Development Aporias - Melo‐Ascencio, Diego Alejandro (Antipode, 2024)
In 2016, Colombia's Constitutional Court declared the Atrato River a subject with rights and named the river's environmental stewards. This article traces how various actors co‐produced the ruling and critically engages scholarly calls to theorise a river‐as‐subject ontology. Centring postcolonial Marxist perspectives, the piece illuminates how power operates through the Rights of Nature discourse and theorises that the river‐as‐subject builds on and creates racialised development aporias: non‐passages beyond the hegemony of the state, capital, and development discourse and double‐binds for environmental justice struggles. Unpacking how the plaintiffs built the case and the river stewards navigated the ruling's first five years, I show that mining‐induced river degradation unfolds through (i) the fraught promise of justice in the Colombian Constitution, (ii) the naturalisation of collective legal personhood as “bio‐cultural rights”, and (iii) the inclusionary exclusion of river stewards from policy discussions about large‐scale mining enclosures and alluvial gold exploitation. Resumen En 2016, la Corte Constitucional de Colombia declaró al río Atrato como sujeto de derechos y nombró a los guardianes del río. Este artículo rastrea cómo varios actores co‐produjeron el fallo y aborda críticamente el llamado académico para teorizar la ontología del río‐como‐sujeto. Centrándose en las perspectivas marxistas poscoloniales, el artículo ilumina cómo opera el poder a través del discurso de los derechos de la naturaleza y teoriza que el río como sujeto reproduce antiguas y crea nuevas aporias del desarrollo racializadas: no‐pasajes más allá de la hegemonía del Estado, el capital y el discurso del desarrollo y situaciones de doble‐filo para las luchas por la justicia ambiental. Al analizar cómo los demandantes construyeron el caso y los guardianes del río navegaron el fallo durante los primeros cinco años, muestro que la degradación del río inducida por la minería se desarrolla a través de [i] la complicada promesa de justicia en la Constitución colombiana, [ii] la naturalización de la personalidad jurídica colectiva como “derechos bio‐culturales” y [iii] la exclusión inclusiva de los guardianes del río de las discusiones sobre cercamientos para la minería a gran escala y la explotación de oro de aluvión.